(SFLVAD]DJ VXJ ELEAMXLMJ XJV MRLP]PLMJV MAL SALEAD]DLMJV FUDAVLAV XRY PJSLAD]DFLRYs - (SVga(Smfnnga(Sulry Oga(Sulga (SLs ((SAxuga(Ssrw(B,s, 2002)
(SSURBNJOAXLVORL DLA XJP MRLP]PLMRSALEAD]DLMJ ELEAMXLMJ FQFNLQJ XJV MRLPRPLMRSALEAD]DLMJV ELEAMXLMJV R URNRV XJV MRLP]PLMJV SALEAD]DLMJVs
(SSURBNJOAXLVORL DLA XJP MRLP]PLMRSALEAD]DLMJ ELEAMXLMJ FQFNLQJ XJV MRLPRPLMRSALEAD]DLMJV ELEAMXLMJV R URNRV XJV MRLP]PLMJV SALEAD]DLMJVs